Developer's Responsibility to Consumers in a Problematic Property Sale and Purchase Agreement - Maria Alberta Liza Quintarti; Lia Fadjriani; Tora Yuliana; Silvester Magnus Loogman Palit (Universitas Muhammadiyah Palu, 2025)
Disputes in property sale and purchase agreements between consumers and developers are increasingly prevalent and often lead to legal conflicts. Common issues include discrepancies between promotional promises and the actual condition of the property, delays in handover, and hidden construction defects that only become apparent after occupancy. This article aims to explore the legal responsibilities of developers when breaches of contract or non-performance (wanprestasi) occur in property transactions. Utilizing a normative legal approach, this study analyzes statutory regulations and relevant court decisions to assess the extent of developers’ obligations. The findings indicate that developers bear full legal responsibility for any violations of the agreement and that consumers are entitled to claim compensation through both civil law provisions and consumer protection frameworks. Strengthening the enforcement of developer accountability is crucial in ensuring fair and transparent property transactions.